Rare Cutaneous Malignancies in Skin of Color. Issue 6 (6th June 2022) - Mosallaei, Daniel; Lee, Erica B.; Lobl, Marissa; Clarey, Dillon; Wysong, Ashley
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: There is a scarcity of information regarding the clinical characteristics of rare cutaneous malignancies in skin of color that has yet to be comprehensively explored. OBJECTIVE: To review and compile the racial differences in epidemiology, clinical presentation, histology, treatments, and outcomes of 3 rare skin cancers: dermatofibrosarcoma protuberans (DFSP), Merkel cell carcinoma (MCC), and sebaceous carcinoma (SC). METHODS: Several searches with keywords denoting specific skin cancer type and race were conducted on PubMed to complete this narrative review. RESULTS: We analyzed 50 sources that were relevant to the initial objective. CONCLUSION: The literature demonstrates that there are nuances in DFSP, MCC, and SC unique to African Americans, Asians/Pacific Islanders, and Hispanics that may differ significantly from Caucasian counterparts. African Americans consistently suffer from the worst clinical outcomes in all 3 rare cutaneous malignancies reviewed. Greater physician awareness and knowledge of the discussed racial differences is the preliminary step to address these disparities.